Analisis Manajemen Kurikulum Sekolah Minggu Buddha dalam Meningkatkan Mutu Pembelajaran: Studi Kasus Sekolah Minggu Buddha Se-Kabupaten Nabire, Provinsi Papua Tengah - Eko Susiono; Alexander Candra (Institut Nalanda, 2024)
The focus of this research is the low quality of learning, the Buddhist Sunday school curriculum has not been implemented, there is no maximum and systematic learning planning, there is no organization, implementation and evaluation of the curriculum, especially non-formal education. To make this happen, one way that can be taken is through managing the Buddhist Sunday School curriculum by adapting the curriculum that has been published by the government and according to the needs of the community. The aim of this research is to determine the management of the Buddhist Sunday School curriculum in Nabire Regency. This research is a type of descriptive qualitative research with a case study approach. Data collection techniques in this research: interviews, observation, and documentation. Data analysis techniques include: data presentation, data reduction and data verification. Data validity testing includes: Data triangulation. The results of this research show that: curriculum management at the Buddha Dharma Karuna Nabire Sunday School (SMB) has been implemented well, starting from planning, organizing, implementing and evaluating, although it is still simple, not optimal and systematic